GLACIOLOGICAL RESEARCH PROGRAM IN EAST QUEEN MAUD LAND, EAST ANTARCTICA PART 2, 1983 - NAKAWO, Masayoshi; NARITA, Hideki; ISOBE, Tamio (National Institute of Polar Research, 1984)
P(論文) departmental bulletin paper